2022
DOI: 10.17309/tmfv.2022.3.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Limb Muscle Explosive Power, Flexibility, and Achievement Motivation on Sickle Kick Performance in Pencak Silat Learning

Abstract: Study Purpose. This study background is that the performance of the sickle kick in Pencak Silat learning is very important to improve the athlete’s performance during the match, both when attacking and defending. The objective is to analyze the performance of the Pencak Silat sickle kick in terms of the quality of physical conditions (such as leg muscle explosive power and flexibility), and psychological elements (such as achievement motivation). Materials and methods. This study involved Pencak Silat at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
(39 reference statements)
2
15
0
Order By: Relevance
“…It is concluded that the combination of these methods significantly increases the efficiency of this procedure. A similar conclusion was made in the study (Ihsan et al, 2022) studied the technique of pencak-silat. The quality of technical elements is determined by both physical and psychological components.…”
Section: Introductionsupporting
confidence: 83%
“…It is concluded that the combination of these methods significantly increases the efficiency of this procedure. A similar conclusion was made in the study (Ihsan et al, 2022) studied the technique of pencak-silat. The quality of technical elements is determined by both physical and psychological components.…”
Section: Introductionsupporting
confidence: 83%
“…So it will be difficult to get an absolute victory by knockout. Therefore, to produce a power punch, appropriate, measurable and systematic training is needed [12] . The amount of punching power also depends on body weight classification, the heavier the boxer's body, the greater the power produced, although this will result in a lack of punching speed [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Speed is the ability to perform similar movements in a row in the shortest possible time, or the ability to cover a distance in the shortest possible time [15]. Front kick / straight [1] is a kick [16] that uses the tip of the foot (base of the toe) with a straight leg, the front kick aims forward at the target by straightening the leg to the toe. The part of the foot that is hit when kicking is the base of the inside of the toes, the position of the body facing the target [1].…”
Section: Introductionmentioning
confidence: 99%